2008
DOI: 10.1002/polb.21416
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization and melting behavior of syndiotactic polypropylenes of different microstructure

Abstract: Syndiotactic polypropylenes and their copolymers with 1‐olefins were synthesized using two metallocene/MAO catalytic systems, and the effect of the different microstructures on nonisothermal crystallization and subsequent melting was studied. Using differential scanning calorimetry (DSC) it was observed that samples with lower content of defects showed crystallization on cooling from the melt, and a double melting peak in the subsequent heating scan, the latter associated with melt, recrystallization and remel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 38 publications
(83 reference statements)
6
15
0
Order By: Relevance
“…The neat polymers presented the (010) reflection at 2θ = 15.9°, whereas the (211) reflection at 2θ = 18.8° was completely absent; this confirmed the disordered form I structure. In a previous article, it was found that a larger number of defects was needed to find the form II in the as‐prepared samples 47. The composites otherwise presented the same diffraction pattern as the pure polymer; this showed that the presence of clay was not able to modify the crystalline structure of the sPP.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…The neat polymers presented the (010) reflection at 2θ = 15.9°, whereas the (211) reflection at 2θ = 18.8° was completely absent; this confirmed the disordered form I structure. In a previous article, it was found that a larger number of defects was needed to find the form II in the as‐prepared samples 47. The composites otherwise presented the same diffraction pattern as the pure polymer; this showed that the presence of clay was not able to modify the crystalline structure of the sPP.…”
Section: Resultsmentioning
confidence: 83%
“…Another characteristic of these samples was the presence of a double melting peak, which was more evident in the samples with low syndiotacticities 22, 43–47. This phenomenon is associated with melt/recrystallization/remelt (MRCRM) processes 44.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This kind of phenomena has been previously observed in neat syndiotactic poly(propylene)s with high amount of defects due to restrictions in the crystallization processes. [64] Therefore, the clay and the compatibilizer can delay the crystallization of some polymeric sequences from the CP7.6OD sample that are able to crystallize on heating scan as reported for syndiotactic samples. [64] There are no relevant differences between the melting temperatures of the samples and their nanocomposites, although all the composites present two melting peaks: the low temperature peak related with the matrix (see Table 3) and the high temperature peak related with the presence of the compatibilizer (%161 8C).…”
Section: Thermal Propertiesmentioning
confidence: 99%